Dynamical decoupling pulses on the quantum correlations for the system of superconducting quantum circuit - 王冬梅 钱懿 许晶波 俞攸红 (Chinese physics B, 2015)
We investigate the influence of the dynamical decoupling pulses on the quantum correlations in a superconducting system consisting of two noninteracting qubits interacting with their own data buses. It is found that the geometric discord and entanglement between the two superconducting qubits can be increased by applying a train of zc-phase pulses. We then proceed to explore how the decoupling pulses affect the quantum transfer of information between the two superconducting qubits by makin~ use of the chance of trace distance.